Updating the Fast Grain Boundary program: Temperature-time paths from intragrain oxygen isotope zoning - Kropf, Gabriel; Bonamici, Chloë; Borchers, Brian (Computers & geosciences, 2021)
This contribution presents a rewritten and expanded version of the Fast Grain Boundary (FGB) program (Eiler et al., 1994) with the motivation of adding to the geochemical tools available for reconstructing temperature-time (T–t) histories that inform studies of tectonics and crustal evolution. Both the original and the new FGB programs model the oxygen-isotope compositional evolution of a rock resulting from diffusive oxygen isotope exchange between minerals. The new FGB program is coded in Python and includes a graphical user interface. Additionally, C-compiled versions of the code are available that provide a 20x speedup of model calculations. The new implementation also allows for inversion of the FGB model to extract unbiased thermal histories from oxygen isotope data. The Levenberg-Marquardt (LM) algorithm is applied to search for cooling histories that maximize agreement between the model output and the measured oxygen isotope data. Tests with synthetic datasets show that the LM algorithm is able to distinguish between simple linear cooling and more complex thermal histories that include reheating events. Inversion of a natural oxygen isotope zoning dataset from titanite shows that, within the resolution of the models and data, the Adirondack Mountains sample location experienced rapid (30–70 °C/m.y.), monotonic cooling from 700 to 500 °C. We develop a heuristic guide to sampling and analytical approaches that improve the resolution of inversion solutions for current SIMS analytical capabilities, and we suggest targets for future improvements of SIMS analysis. Our tests indicate that the current SIMS analytical precision for in situ oxygen isotope measurements is sufficient to allow for temperature-time path recovery with thermal resolution of 25–50 °C and temporal resolution of 2–3 million years. •Fast Grain Boundary program (Eiler et al., 1994) re-written in Python and C.•Addition of a graphical user interface.•Ability to invert oxygen isotope zoning profiles for T–t paths.•Tests for functionality and sensitivity with synthetic and real oxygen isotope data.